Viable SARS-CoV-2 Omicron sub-variants isolated from autopsy tissues - Maffia Bizzozero, Santiago (2023)
Pulmonary and extrapulmonary manifestations have been described after infection with SARS-CoV-2, the causative agent ofcoronavirus disease 2019 (COVID-19). The virus is known to persist in multiple organs due to its tropism for several tissues.However, previous reports were unable to provide definitive information about whether the virus is viable and transmissible. Ithas been hypothesized that the persisting reservoirs of SARS-CoV-2 in tissues could be one of the multiple potentially overlappingcauses of long COVID. In the present study, we investigated autopsy materials obtained from 21 cadaveric donors with documentedfirst infection or reinfection at the time of death. Among the cases, there were COVID-19 vaccine recipients including differentformulations and doses received. The aim was to find the presence of SARS-CoV-2 in the lungs, heart, liver, kidneys, and intestines.We used two technical approaches: the detection and quantification of viral genomic RNA using RT-qPCR, and virus infectivity usingpermissive in vitro Vero E6 culture. All tissues analyzed showed the presence of SARS-CoV-2 genomic RNA, but at dissimilar levelsranging from 1.01x102 copies/mL to 1.14x108 copies/mL, even among those cases who had been COVID-19 vaccinated. Importantly,different amounts of replication-competent virus were detected in the culture media from the studied tissues. The highest viralload levels were measured in the lung (~1.4x106 copies/mL) and heart (~1.9x106 copies/mL) samples. Additionally, based on partialSpike gene sequences, SARS-CoV-2 characterization revealed the presence of multiple Omicron sub-variants exhibiting a high levelof nucleotide and amino acid identity among them. These findings highlight that SARS-CoV-2 can spread to multiple tissue locationssuch as the lungs, heart, liver, kidneys, and intestines, both after primary infection and after reinfections with the Omicronvariant, contributing to extending knowledge about the pathogenesis of acute infection, and understand the sequelae clinicalmanifestations that are observed during post-acute COVID.